Fundamentalismo religioso versus racionalismo y modernidad - Paz y Miño Conde, Manuel (2020)
Fundamentalism conceived as the fanatic and extreme expression of a religious (and / or political) ideology that considers itself as having an unequivocal truth, because it is believed to come from above, is not a new phenomenon, it is latent in any religion. Fundamentalism arises as a reaction, which can even be violent, to the change of mentality and customs produced by people who are considered sinners, evil, deceived or demonized. In circumstances of great ignorance and material need fundamentalists will grow in number, but that does not prevent them from arising in any social class or time. Only an early humanist and scientific education can foresee the emergence of fundamentalist groups within a society, or at least do so in a large number of them.